Methylglyoxal effects on protein aggregation and amyloid formation - Oliveira, Luís Miguel Araújo da Silva, 1982- (2009)
Tese de doutoramento, Bioquímica (Biofísica Molecular), 2010, Universidade de Lisboa, Faculdade de Ciências